Relação da soroprevalência do Helicobacter pylori com a psoríase e sua gravidade - Mesquita, Priscila Miranda Diogo (2015)
Objectives: Psoriasis is a chronic inflammatory disease that affects the skin and joints and has a multifactorial etiology. Recently, it has been suggested that Helicobacter pylori infection may contribute as a trigger for the development of the disease. The aim of this study was to determine the prevalence of Helicobacter pylori seropositivity in patients with psoriasis and to evaluate the relationship between disease severity and H. pylori infection. Methods: H. pylori infection was assessed in psoriatic patients and controls by using H. pylori IgG quantitative enzyme immunoassay (ELISA test). The patients were classified according to the severity of the disease (PASI score). Results: One hundred and twenty six psoriatic patients (73 females and 53 males); mean age 50.48 years; 65 patients (51.59%) had severe psoriasis, 40 (31.75%) moderate psoriasis and 21 (16.67%) mild psoriasis. Twenty one healthy volunteers included as a control group, mean age of 41.05 years, 13 females and 8 males. One hundred and eleven psoriatic patients tested serologically, 80 (72.07%) were seropositive compared to 7 positive volunteers (33.33%) (P = 0.0023). Forty nine (75.38%) patients with severe psoriasis were positive, 25 (62.50%) with moderate psoriasis were positive and 6 (28.57%) with mild psoriasis were positive (P = 0.02). Conclusion: The Helicobacter pylori infection influences the development of psoriasis and severity of the disease.